Body Mass Index and Post-dural Puncture Headache in the Obstetric Population: is there any link? - Vaz Antunes, Maria; Moreira, Adriano; Faria, Aida (Journal of the Portuguese Society of Anesthesiology, 2017)
Introdution Post-dural puncture headache (PDPH) is one of the most common complications of neuraxial blockade. In obese pregnant women, the epidural technique is more difficult to perform, with a higher block failure rate and risk of accidental dural puncture (ADP). The aim of our study was to evaluate the relationship between body mass index (BMI) and the development of PDPH. Material and Methods We conducted a retrospective study between January 2007 and December 2014. We reviewed the record sheets of patients who experienced ADP/PDPH. Patients were divided into two groups according to BMI, non-obese (BMI < 30 kg/m2, G<30) and obese (BMI ≥ 30 kg/m2, G ≥ 30). We used SPSS 22.0 for statistical analyses. Results There were 58 ADP (0.3%) and 45 (77.6%) women developed PDPH. Comparing G < 30 (n = 35) and G ≥ 30 (n = 23), the incidence of PDPH was similar (80.0% vs 73.9%, p > 0.05). Severe PDPH occurred in 4 (11.4%) women in G < 30 and did not occur in G ≥30 (p > 0.05). Conservative treatment was performed in all patients. The epidural blood patch (EBP) was performed in 42.9% in G < 30 and 17.4% in G ≥ 30 (p = 0.043, OR 3.563; 95% CI 1.00-12.67). After redefinition of groups of women with BMI < 40 kg/m2 and IMC ≥ 40 kg/m2, there was no difference in the incidence and intensity of PDPH, or the need to perform EBP. Discussion Low level of evidence suggests that the risk of PDPH decreases as the BMI increases. In our study, the incidence and characteristics of PDPH were similar in obese and non-obese women, but the need for an EBP was lower in obese pregnant women, suggesting that BMI may be protective. Conclusion There was no evidence that obese patients are less prone to the development of PDPH. However, obesity was associated with lower need of EBP.